(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
To further examine the effect of the strain rate on the behaviour of hoop-confined reinforced concrete (RC) columns, the dynamic behaviour of overlapping hoop-confined RC columns subjected to lateral rapid loadings is investigated by applying finite element analysis. Based on the verified finite element model, the effect of the following five parameters on the dynamic behaviour of RC columns were discussed considering both strain rate effect and confinement effect: the loading rate, axial load ratio, volume ratio of stirrups, shear span ratio and configuration of hoops. The following conclusions were made. The lateral-load-carrying capacity increases and the ductility decreases because of the rapid loadings, but the increase in volume ratio of the stirrups weakens the effect of the loading rate on the ductility. The axial load ratio and volumetric ratio of the stirrups affect the dynamic increasing factor (DIF) of the lateral-load-carrying capacity, but the effect of the shear span ratio on the DIF can be neglected. The increase in flexural-load-carrying capacity due to the increase in volume ratio of the stirrups under static loadings is higher than that under rapid loadings. The difference in effect of the two configurations of overlapping hoops on the dynamic behaviour of RC columns is notably small.